Trading regularity and fund performance: Evidence in uncertain markets - TONG, Lin (Institutional Knowledge at Singapore Management University, 2020)
High trading regularity funds outperform low trading regularity funds more during periods of low market returns and greater market and economic uncertainty. Their trading also has strong return predictability on stock returns during periods of greater uncertainty. They trade more around news events, and their news related trading predicts stock return stronger during periods of greater uncertainty. They also profit from liquidity provision in highly uncertain market environment. Overall our evidence suggests that high trading regularity funds trade more frequently during periods of high uncertainty when information production and processing skill is more valuable and when the demand for liquidity is high.